2019
DOI: 10.1007/s42452-019-0630-1
|View full text |Cite
|
Sign up to set email alerts
|

Regression methods in the calibration of low-cost sensors for ambient particulate matter measurements

Abstract: The article presents comparison of regression methods used to obtain calibration formulas for low-cost optical particulate matter sensors. Data for analysis were taken from 1-year collocation study of PMS7003 sensors (Plantower) with researchgrade instrument TEOM 1400a. The PM 2.5 fraction was considered in this study. The results of measurements showed that PMS7003 was characterized by high reproducibility between units (coefficient of variation was lower than 10%), but the raw sensor outputs significantly ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 44 publications
0
39
0
2
Order By: Relevance
“…Therefore, low-cost sensors with high relative humidity must be established to eliminate the possibility of problematic observations. Multi-variable models may be fitted to obtain reasonable formulas, which can be easily interpreted and implemented from each sensor 22 . However, the current spatial calibration model performs the best (4.8 μg/m 3 ), because the model is already considered a local weighting for the spatial heterogeneity of calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low-cost sensors with high relative humidity must be established to eliminate the possibility of problematic observations. Multi-variable models may be fitted to obtain reasonable formulas, which can be easily interpreted and implemented from each sensor 22 . However, the current spatial calibration model performs the best (4.8 μg/m 3 ), because the model is already considered a local weighting for the spatial heterogeneity of calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the weighting factors, sensor manufacturers calculate values to correct for certain effects, such as the fact that OPS cannot detect particles which are too small. Laboratory tests and calibrations of OPS are performed under controlled conditions with known particles, such as polystyrene latex spheres (Walser et al, 2017;Bezantakos et al, 2018), continuously changing monodisperse particles (Kuula et al, 2017;Kuula et al, 2020) or multi-modal particles (Cai et al, 2019). A burning chamber is used in some investigations as well (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We did not perform collocation tests for our sensors, but based our decisions on laboratory tests that have been conducted by the US Environmental Protection Agency as well as independent researchers who have shown that the PMS7003 factory calibration demonstrates low intramodel variability and strong correlation with reference instruments (a coefficient of variation less than 10% between units) [14], [15], [25]. Both PM and CO2 sensors are reported to be sensitive to environmental conditions, such as humidity and temperature, so we use these metrics to validate data points, but also report these metrics with our data set for future studies [26], [27].…”
Section: Methodsmentioning
confidence: 99%
“…The "community science" approach has become more feasible than ever in recent years due to the release of low-cost and high-precision sensors which can consistently measure particulate matter among other pollutants. While these sensors should still be properly calibrated with reference instruments before having their accuracy assumed, their performance is a marked improvement over past generations, especially considering their price, size, and power consumption as attested by laboratory tests by independent researchers and the EPA [14], [15]. Along with these new sensors have come new proven transmission technologies such as LoRaWAN, enabling scientists and citizens to not just collect data but also reliably transport it to high performance computing infrastructures for processing [16].…”
Section: Literature Reviewmentioning
confidence: 99%